PROSES PEMBELAJARAN PADA SEKOLAH DASAR INKLUSI - Dwi Yanti Viona Putri (Universitas Negeri Padang, 2012)
This research is plane from the term inclusi trend right now. In SDN 47 Talawi Payakumbuh is found a blind child, teacher class and a Guru Pembimbing Khusus (GPK) are a blind too. In mathematic education process, the blind have a trouble to understand the matery, because of teacher class can’t understand the blind child characteristic, till in mathematic education process, not adjust RPP with child characteristic and not yet prepare the exact evaluation to the blind child too. Till low, the average of the child is 50-60. So this research is process for blind child, the constraints must be up against in education process and efforts to surpass the constraint in mathematic education process. This research use qualitative approach with qualitative descriptive research type. Subyect of the research is a teacher class, data source support is special cainselor teacher and the headmaster in SDN 47 Talawi Payakumbuh. Collecting data process are pass trought by observation, interview, and documentation. The yield process indicate in education process, teacher not adjust RPP with the characteristic of the blind child. In the realization once in a while use exact media till in mathematic education process. The child feel difficult to understand the matter. The constraint become because the teacher not yet understand characteristic of the blind child, till result the child always get low value in mathematic lesson. The effort in experience constraint is with always prepare real media of concrete, concord with lesson matter. The teacher must always prepare concrete media and realize modification to make RPP is concord with characteristic of the blind child. Coming on X can increase teaching method is concord with characteristic of the blind child, and more prepare supporting media in the education process.